2008
DOI: 10.1590/s0102-79722008000100002
|View full text |Cite
|
Sign up to set email alerts
|

Que perfil da família biológica e adotante, e da criança adotada revelam os processos judiciais?

Abstract: ResumoA adoção de crianças necessita ser estudada em seus aspectos legais, psicológicos, socioculturais. Este estudo tem o objetivo de caracterizar as crianças, as famílias adotantes e biológicas, envolvidas em processos de adoção em Ribeirão Preto-SP, de 1991 a 2000. Cento e dez processos judiciais foram analisados através de uma estatística descritiva. Constatou-se a prevalência das adoções "prontas", nas quais os adotantes requerem na Justiça a adoção de uma criança, que conheceram através de mediadores ou … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
3
0
15

Year Published

2010
2010
2018
2018

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(21 citation statements)
references
References 2 publications
1
3
0
15
Order By: Relevance
“…This percentage is similar to that evidenced by Mariano and Rossetti-Ferreira (2008), whose research showed that 70% of children adopted were under one year of age. Based on the concepts of interdependence and care defended by the social model (Diniz, 2003;Kittay et al, 2005;Mello & Nuernberg, 2012), it is possible to understand how a greater dependence on special care required by the child with disabilities can contribute to speeding up the adoption of these children.…”
Section: Conceptions Of Disability and Their Influences On The Formalsupporting
confidence: 88%
See 1 more Smart Citation
“…This percentage is similar to that evidenced by Mariano and Rossetti-Ferreira (2008), whose research showed that 70% of children adopted were under one year of age. Based on the concepts of interdependence and care defended by the social model (Diniz, 2003;Kittay et al, 2005;Mello & Nuernberg, 2012), it is possible to understand how a greater dependence on special care required by the child with disabilities can contribute to speeding up the adoption of these children.…”
Section: Conceptions Of Disability and Their Influences On The Formalsupporting
confidence: 88%
“…This disparity appears to be justified, primarily, by the profile of the child required by the applicants: white, newborn and healthy (Amin & Menandro, 2007;Fonsêca, Santos & Dias, 2009;Silveira, 2005). Not all adoptions in the Brazilian context may have been accounted for by the CNA, given the occurrence of "ready adoptions", when there is a legal form of adoption that has been previously defined (Mariano & Rossetti-Ferreira, 2008;RossettiFerreira et al, 2012). In the Brazilian legislation, with the establishment of Law No.…”
mentioning
confidence: 99%
“…Em relação à escolaridade, apenas uma pessoa não concluiu o ensino fundamental (Tabela 1). Em termos da parentalidade adotiva, enquanto quatro casais (1, 2, 4 e 5) passaram pelo processo de adoção que envolve a lista de espera preconizada pela lei, três casais (3, 6 e 7) obtiveram a guarda de uma criança conhecida, configurando o que é conhecido como adoção direta (Mariano, & Rossetti-Ferreira, 2008).…”
Section: Resultsunclassified
“…Há uma grande disparidade entre o volume de informações disponíveis sobre as famílias acolhedoras e a ausência de dados sobre as de origem. Semelhante situação de ausência de registro também foi apontada em pesquisas sobre acolhimento institucional e adoção, nos quais também não consta um sistema de registro de informações sobre as crianças e suas famílias de maneira interligada e articulada (Mariano & Rossetti-Ferreira, 2007;Serrano, 2008). Pode-se pensar que a falta de registros deva-se ao fato de não haver inicialmente uma proposta do programa de realizar um trabalho voltado para essas famílias, que eram encaminhadas à rede de serviços municipais, especialmente aqueles vinculados à saúde, à educação e à promoção social.…”
Section: Famílias De Origemunclassified